Examines Iran-China Trade Relations: COVID-19 Challenges, Sanctions, and Positive Potentials - Azim Jelodar; Pingfang Duan (The Institute of Academic Research and Publication (IARP), 2022)
Article in English. In the field of international relations, governments use different tools to advance their national goals and interests, some of which are tangible and some of which are immaterial. In a way, these tools mainly indirectly affect the important interests of rival governments and cause them to change their behavior. At a time when the use of force in international relations has diminished or at least governments are more cautious in relying on this tool, the impact on sensitive areas has taken another form, which is a manifestation of sanctions. Sanctions imposed on Iran in recent years over its nuclear program have affected Iran's relations with other countries and thus its interests. Following the sanctions, Iran lost ties with many countries, especially European countries, and thus accelerated Iran's growing relations with China, especially in the fields of economy and trade. Therefore, in this paper, we investigated the positive capacity for cooperation between Iran and China and suggest seven effective criteria based on the objectives of this study.